Flattening the infection curve – understanding the role of telehealth in managing COVID-19. Issue 2 (23rd April 2020) - Leite, Higor; Gruber, Thorsten; Hodgkinson, Ian R.
Abstract : Purpose: This paper aims to discuss the strategic role of telehealth technologies in managing the COVID-19 pandemic. Design/methodology/approach: This is a viewpoint paper, based on opportune information published and discussed by scholars and managers from different sources; the authors gathered this information to discuss the implications of telehealth during the outbreak. Findings: Based on examples and benchmarking, the authors found that it is possible to lean on telehealth technologies as a frontline ally to avoid the spread of the virus by tracking, testing and treating (3T's model). Research limitations/implications: Together with information published on COVID-19, the authors present their critical observations on the use of telehealth. However, the authors acknowledge that there are restrictions on the use of new technologies in health-care practices that were not addressed by this paper, and they suggest further research to address this limitation. Practical implications: Governments, health-care organizations and managers are encouraged to take advantage of the information published in this paper. One of the benefits of telehealth is the possibility of bringing patients and physicians together virtually, without the need for physical contact. Henceforth, the authors suggest a more comprehensive implementation of best practices from telehealth to relieve congested health-care facilities and to avoid the risk of further infection. Social implications: The economic and social impacts of the virus are considered unprecedented by governments worldwide. Therefore, the authors advocate that telehealth practices embedded in health-care practices relieve the pressure that naturally arise during this type of critical event. Originality/value: In this timely paper, the authors provide invaluable information related to the impact of telehealth technologies on flattening the infection curve of COVID-19.